1988
DOI: 10.3109/00498258809041723
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of drug-metabolizing enzymes in humans

Abstract: 1. The activities of the ethoxycoumarin O-deethylase (ECOD), epoxide hydrolase (EH), UDP-glucuronyl transferase (GT), glutathione S-transferase (GST), acetyl transferase (AT) and sulphotransferase (ST) were measured in 6 liver, 8 lung, 8 kidney, 8 intestinal mucosa and 22 urinary bladder mucosa specimens from human subjects. EH and GT were studied with styrene oxide and 1-naphthol, respectively, as substrates, GST, AT and ST were studied with benzo(a)pyrene-4,5-oxide, p-aminobenzoic acid and 2-naphthol, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
74
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(80 citation statements)
references
References 21 publications
5
74
0
1
Order By: Relevance
“…These transferases exhibit distinct but overlapping substrate specificity and are known to catalyze the glucuronidation of a variety of phenols, arylamines, steroids, and bilirubin. Enzymatic activity is highest in the liver, followed by kidney and intestinal mucosa (42). We have shown that human liver microsomes can catalyze the N-glucuronidation of several N-hydroxyarylamines, including those derived from ABP and 2-naphthylamine (43), and from IQ, MeIQx, PhIP, and Glu-P-1 (44).…”
Section: Udp-glucuronosyltransferasesmentioning
confidence: 99%
See 1 more Smart Citation
“…These transferases exhibit distinct but overlapping substrate specificity and are known to catalyze the glucuronidation of a variety of phenols, arylamines, steroids, and bilirubin. Enzymatic activity is highest in the liver, followed by kidney and intestinal mucosa (42). We have shown that human liver microsomes can catalyze the N-glucuronidation of several N-hydroxyarylamines, including those derived from ABP and 2-naphthylamine (43), and from IQ, MeIQx, PhIP, and Glu-P-1 (44).…”
Section: Udp-glucuronosyltransferasesmentioning
confidence: 99%
“…Phenol sulfotransferases, which catalyze the sulfate conjugation of catechol and phenolic drugs and other xenobiotics, have been studied in several human tissues, including the liver, small intestine, cerebral cortex, kidney, and blood platelets (42,51). Two forms of sulfotransferase have been characterized: a thermolabile (TL) form that catalyzes the sulfation of dopamine and other phenolic monoamines and is relatively resistant to inhibition by 2,6-dichloro-4-nitrophenol; and a thermostable (TS) form that catalyzes the sulfation of a variety of phenols, such as p-nitrophenol, and is highly sensitive to 2,6-dichloro-4-nitrophenol inhibition.…”
Section: Sulfotransferasesmentioning
confidence: 99%
“…Family 2 enzymes include UGT2A1, 2B4, 2B7, 2B10, 2B11, 2B15 and 2B17, encoded by separate genes, mapped on chromosome 4 [14]. Most human UGT isoforms are expressed in the liver, but high UGT expression levels have also been reported extrahepatically, indicating that other organs also play a major role in glucuronidation [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to nonenzymatic conjugation with GSH, glutathione S-transferase (GST) isoforms, which are expressed ubiquitously throughout the body (Pacifici et al, 1988;de Waziers et al, 1990;Awasthi et al, 1994;Rowe et al, 1997), accelerate GSH conjugation by lowering the pKa of the sulfhydryl group of GSH from 9.0 to 6.2-6.7 and increasing the cytosolic concentration of deprotonated GSH (Armstrong, 1997;Fabrini et al, 2011). Therefore, both nonenzymatic and GST-dependent GSH conjugation of the acrylamide moiety in extrahepatic organs as well as in the liver is likely to play a significant role in the pharmacokinetics (PK) of TCI compounds.…”
Section: Introductionmentioning
confidence: 99%